Estudio de la capacidad portante de los suelos del centro poblado las Palmas, distrito de la Sanda de Shilcayo - Villalobos Ríos, Rodolfo Armando (2014)
This thesis has been developed in the Academic Professional School of Civil Engineering, Faculty of Civil Engineering and Architectüre, National University of San Martin - Tarapoto, far purposes of certification as a Civil Engineer;with the working point the Town Centre Las Palmas, District Shilcayo province and San Martin Region. The research was conducted to study, identify and evaluate soil types that exist in the urban area of the Town Centre and to determine their bearing capacity, far use in the · construction of buildings, looking far practica! and scientific solutions to the problem of building without knowing the Real soil behavior; settlement and avoiding deterióration of buildings affecting the ornament ánd therefare the quality of life of users; among others. So is actively involved in the production of new knowledge for positive purposes of the community and science. Fundamental concepts required in the area of Soil Mechanics and Geotechnical and using special equipment and accessories Referential Laboratory of our University were applied soil classification was obtained and thereby its fundamental charácteristics far both sandy and cohesive · found; based on the theory of · Terzaghi and with the fundamental contribution of the direct shear machine , the required parameters of friction angle () and cóhesion (C) , basic were obtained to determine the bearing capaeity of soils under study , not having shown the presence of thewater table at depths up to 3 m. As achievements, indicated that the results obtained show dearly that is possible, from the correct application of the theory, research and convincing results, which can be presented as an altemative technique far calculating the désired bearing capacity. The validation of the hypothesis of this research is accomplished with the support of lnferential Statistics with accuracy of 5%, indicating thatthe values of bearing capacity of the soils studied are highly significant and allows us to affirm that are sure to cement buildings vegetative growth and urban devélopment and aware of our social responsibility as part of the National University of San Martin, we are helping to salve the ·problems and to economic and social development of the community, and therefare of our country, as well to ensure that our knowledge is put into practice and develop our sense of professional career.